(untitled) (Swiss Medical Weekly, 2011)
Cell death is a ubiquitous process whose immunological consequences can influence the course of infectious, autoimmune and inflammatory diseases. While cell death has long been dichotomised in terms of apoptosis and necrosis, other forms of death can occur and they vary in their capacity to stimulate as well as inhibit inflammation. The pro-inflammatory activity of dead cells results from a wide variety of intracellular molecules that are released as cell permeability increases during death. These molecules have been termed as DAMPs (damage associated molecular patterns) or alarmins. Among these DAMPs, HMGB1, a non-histone nuclear protein, serves as the prototype. Although HMGB1 was originally thought to act alone as a cytokine, recent studies suggest that its immunological effects result from complexes of HMGB1 with either other DAMPs or with PAMPs (pathogen associated molecular patterns). Studies on the role of HMGB1 in pathogenesis suggest that the formation of extracellular complexes is an important mechanism for generating pro-inflammatory signals during cell death and therefore could be a potential target of new therapy.